2015
DOI: 10.1111/ejn.13005
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to promote peripheral nerve regeneration: electrical stimulation and/or exercise

Abstract: Enhancing the regeneration of axons is often considered a therapeutic target for improving functional recovery after peripheral nerve injury. In this review, the evidence for the efficacy of electrical stimulation (ES), daily exercise, and their combination in promoting nerve regeneration after peripheral nerve injuries in both animal models and in human patients, is explored. The rationale, effectiveness, and molecular basis of ES and exercise in accelerating axon outgrowth are reviewed. In comparing the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
194
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(213 citation statements)
references
References 124 publications
4
194
0
1
Order By: Relevance
“…The answer to the question is generally assumed to be that regenerating axons fail to reinnervate target muscles due to irreversible denervation atrophy with ultimate fat replacement [2,25,28]. Experimentally, we asked the question of the consequences of the long periods of isolation of the injured neurons that regenerate their lost axons from their denervated targets (chronic axotomy of the neurons), the long periods of denervation of the Schwann cells in the distal nerve stumps (chronic Schwann cell denervation), and, finally, the chronic denervation of the muscles (chronic muscle denervation).…”
Section: The Window Of Opportunity For Nerve Regeneration Is Restrictedmentioning
confidence: 99%
“…The answer to the question is generally assumed to be that regenerating axons fail to reinnervate target muscles due to irreversible denervation atrophy with ultimate fat replacement [2,25,28]. Experimentally, we asked the question of the consequences of the long periods of isolation of the injured neurons that regenerate their lost axons from their denervated targets (chronic axotomy of the neurons), the long periods of denervation of the Schwann cells in the distal nerve stumps (chronic Schwann cell denervation), and, finally, the chronic denervation of the muscles (chronic muscle denervation).…”
Section: The Window Of Opportunity For Nerve Regeneration Is Restrictedmentioning
confidence: 99%
“…It has been demonstrated that exercise and electrical stimulation both promote peripheral nerve regeneration, 25 and an explanation for this finding might be that both of them enhance neuroplasticity.…”
Section: Fig 10mentioning
confidence: 99%
“…Recently, low-intensity electrical stimulation has attracted more and more attentions, and its effects have been investigated widely (Deans et al 2007;Anastassiou et al 2010;Gordon and English 2016). Some studies have proposed SR as a key mechanism in optimizing the performance of specific functional electric stimulation devices, such as hearing implants (Morse and Roper 2000;Zeng et al 2000).…”
Section: Introductionmentioning
confidence: 99%